FERTILITY AND PARENTING OPTIONS IN TURNER SYNDROME - A REVIEW OF CURRENT POTENTIAL AND LIMITATIONS - Aleksandra Dzwonkowska,; Paulina Redel, (International Journal of Innovative Technologies in Social Science, 2025)
Turner syndrome (TS) is a chromosomal disorder with a prevalence of 1 in 2,500 live births. The most common karyotype is 45.X, however, mosaic karyotypes are also present and are associated with a milder presentation of the syndrome. The main symptoms faced by patients with TS include growth deficiency, cardiovascular disorders, and reproductive disorders, including premature ovarian failure (POI). Fertility disorders are mainly due to the presence of dysgenetic gonads, which negatively affect the development of secondary sexual characteristics. Changes in the ovarian cells, including stunted follicle development, abnormal morphology, and follicle atresia, are also a significant problem. Measurements of FSH, LH, and AMH, which appear to be the most stable parameters of ovarian reserve, play an important role in the diagnosis of POI. Due to the fertility disorders in TS, spontaneous pregnancies are achieved in less than 6% of women. Among the fertility preservation methods in patients with preserved ovarian reserve are oocyte cryopreservation or cryopreservation of ovarian tissue, while oocyte donation is the method of choice when ovarian reserve is depleted. For women desiring offspring with contraindications to pregnancy, surrogacy or adoption are alternatives. Pregnancy in TS is associated with many risks for both the mother and the fetus. Patients should be managed by a specialised team experienced in the management of women with TS, including cardiac assessment, both preconceptional and postconceptional. This review discusses the available parenting methods for patients with TS, taking into account recent literature.